Functional and structural analyses of IMP-27 metallo-β-lactamase: evolution of IMP-type enzymes to overcome Zn(II) deprivation - Yoshiki Kato; Toshio Yamaguchi; Haruka Nakagawa-Kamura; Yoshikazu Ishii; Akiko Shimizu-Ibuka (Microbiology Spectrum)
ABSTRACT IMP-type metallo-β-lactamases are di-Zn(II) enzymes that can inactivate a wide range of bicyclic β-lactam agents used in clinical practice. IMP-27 shares 82% amino acid sequence identity with IMP-1, the first IMP-type enzyme identified. Herein, we conducted structural determination, kinetic, and chelating agent resistance analyses of IMP-27. Once determined, IMP-27 was then compared to its mutant, namely, G262S, and IMP-1. Crystallographic structural analysis of IMP-27 showed an overall structure comparable to that of IMP-1 and other IMP-type enzymes; the positions of the zinc (Zn) ions varied across enzymes. Kinetic analysis showed that IMP-27 had lower catalytic efficiency against penicillins, ceftazidime, cephalexin, and imipenem than IMP-1; however, it had higher affinity and catalytic efficiency against meropenem, especially in the presence of Zn(II). This suggests that the catalytic site of IMP-27 is optimized to hydrolyze meropenem during molecular evolution at the expense of catalytic efficiency against penicillins. However, Zn(II) content analysis after EDTA treatment revealed no significant difference between enzymes. Moreover, analysis of IMP-27 mutants indicated that the differences in kinetic properties and chelator resistance between IMP-1 and IMP-27 were mainly due to an amino acid substitution at position 262.IMPORTANCEThe residue at position 262 has been reported as a key determinant of substrate specificity in IMP-type enzymes. Among more than 80 IMP-type metallo-β-lactamase (MBL) variants, IMP-27 was the first reported IMP-type MBL isolated from Proteus mirabilis. This enzyme has a glycine residue at position 262, which is occupied by serine in IMP-1. Compared with IMP-1, IMP-27 had a significantly higher affinity and catalytic efficiency against meropenem and improved metal-binding capacity, maintaining its activity under Zn(II)-limited conditions better than IMP-1. The analysis of the IMP-27 mutants indicated that differences between IMP-27 and IMP-1 were mainly due to an amino acid substitution at position 262. In the case of IMP-27, the G262S mutation optimized the catalytic site of IMP-27 for meropenem hydrolysis, at the expense of catalytic efficiency against penicillins.